Clinical Characteristics of Patients with Pericardial Effusion - Bista, Madhab; Nepal, Rajesh; Aryal, Manoj; Katwal, Sushant; Thakur, Manoj Kumar (Journal of Nobel Medical College, 2021)
Background: Pericardial effusion (PE) is one of the common pericardial diseases in our population with its associated morbidity and mortality. Our study aims to evaluate the   clinical characteristics of patients with PE from eastern region of Nepal.Materials and Methods: A descriptive cross-sectional study carried out in tertiary care center in eastern region of Nepal from March 2019 to February 2020. A total of 45 cases of PE were enrolled by convenient sampling method. Diagnosis was made based on clinical history, examination, and relevant laboratory investigations. Data was entered in Microsoft excel 2007 and converted into IBM SPSS data editor, version 20.Results: Forty five patients were included with mean age of 55.36 ± 16.38 years. Twenty seven patients (60%) were male and 18 (40%) were female.  Hypertension was present in 12 (26.7%) and diabetes mellitus in 13 (28.9%).  Mean serum hemoglobin was 10.85 ± 2.09 gm/dl. Chronic kidney disease (Uremia), tuberculosis and hypothyroidism were the common causes of PE. Common clinical symptoms were dyspnea, fever, and cough and chest pain. Moderate to large pericardial effusion was noted in 21 (46.7%) of patients. Cardiac tamponade was present in 6 (13.3%). Twenty seven patients (60%) patients underwent pericardiocentesis.Conclusion: Chronic kidney disease, tuberculosis and hypothyroidism were the common causes of PE with male predominance. Dyspnea was the most common presenting symptom.  Cardiac tamponade was relatively less common.